'If you are feeling alone and you are not feeling safe, it impacts everything': a mixed-methods exploration of international students' accommodation, subjective wellbeing and mental health help-seeking - Tim Corney; Karin du Plessis; Brett Woods; Catherine Lou; Anita Dewhurst; Daveena Mawren (BMC, 2024)
Abstract Background The international education sector is important not only to Australian society, but also to the national economy. There are growing concerns about the potential wellbeing challenges facing international students in their host country, owing to acculturative stress; including loneliness, isolation and experiences of racism. Risks include poor mental health and decreased likelihood to access support due to stigma, language and cultural barriers, not knowing where to seek help, and poor mental health knowledge. Methods This study explored students' perceptions of their accommodation, subjective wellbeing (through the Personal Wellbeing Index, ['PWI']), mental health help-seeking and individual engagement with evidence-based everyday health promotion actions (informed by the '5 Ways to Wellbeing' model) through an online survey (N = 375) and three online focus groups (N = 19). A mixed-methods approach using descriptive statistics, ANOVA, regression analysis and thematic analysis, were used. Results The PWI of international students in the survey was observed to be substantially lower (M = 60.7) than that reported for the Australian population (M = 77.5). Accommodation impacted on wellbeing (loneliness, belonging, connectedness) in a number of different ways including through location, safety, and shared accommodation. In terms of help-seeking, international students noted a number of barriers to accessing support for mental health: cost of accessing support, language and cultural barriers, lack of information on where to find support and stigma. Conclusions In the discussion, implications of the findings are considered, including that more could be done to shape policy and practice in service and facility provision around wellbeing, connectedness, and help-seeking for mental health support of international students.